Assistance In Utilizing The Potential Of Local Kalimantan Flora As Biology Instructional Media For High School Teachers In Samarind - Linda Oktavianingsih; Medi Hendra; Kadek Subagiada; Muhammad Fauzi Arif; Mukhlis Mukhlis; Alya Nindytias Utami; Dina Hayati Putri; Novita Arumsari; Dewi Rahmawati; Riezdqhy A. Farahiyah Al Husna (UNIVERSITAS MUHAMMADIYAH MATARAM, 2026)
Biology learning requires a contextual approach that connects theoretical concepts with real environmental conditions. Despite the rich biodiversity of Kalimantan, high school biology teachers in Samarinda often rely heavily on conventional textbooks, limiting students' direct exploration of local ecosystems. This community engagement program aimed to assist high school biology teachers in utilizing local flora as biology instructional media through interactive training, focus group discussions, field-based plant identification, and herbarium-making practice. The program's effectiveness was measured using a pre-test and post-test design involving 15 participating teachers. The results showed an increase in the mean knowledge score from 78.7 in the pre-test to 89.3 in the post-test, with an N-gain of 0.50 (medium category) and a statistically significant improvement (paired t-test, p = 0.012). The proportion of participants achieving mastery (score ≥75) rose from 73.3% to 93.3%, and all participants successfully designed local flora-based biology instructional media. In conclusion, integrating local biodiversity into classroom learning not only enhances teachers' pedagogical competence and makes biology more meaningful, but also fosters environmental conservation awareness among educators and students in East Kalimantan.